PERAN KOMPETENSI DALAM MEMEDIASI HUBUNGAN PENDIDIKAN, PELATIHAN, DAN PENGALAMAN TERHADAP PRODUKTIVITAS SUMBER DAYA MANUSIA DI NOVUS GIRI RESORT & SPA PUNCAK CIANJUR - Arifin, Zainul; Hwihanus, Hwihanus (JURNAL LENTERA BISNIS, 2026)
Increasing the productivity of human resources (HR) in the competitive hospitality industry, especially through strengthening the factors that shape employee competence. The purpose of this study is to analyze the influence of education, training, and work experience on competencies, as well as their implications on human resource productivity at Novus Giri Resort & Spa Puncak Cianjur, including the role of competence as a mediating variable. The method used is a quantitative approach with Structural Equation Modeling (SEM) analysis techniques. The research sample consisted of 100 respondents who were employees, with data collection techniques through questionnaires. Model testing was carried out using goodness of fit tests, direct, indirect, and total effect tests. The results of the study show that education, training, and work experience have a positive and significant effect on competence. Competency has also been shown to have a positive and significant effect on human resource productivity, and acts as a mediating variable in the relationship between the three independent variables on productivity. Training is the most dominant factor in increasing competence and productivity, followed by work experience, while education tends to have an indirect effect through competence. The conclusion of this study confirms that increasing human resource productivity is more effectively done through a competency-based approach. Therefore, it is recommended that companies prioritize structured and needs-based training programs, as well as optimize work experience-based learning to continuously improve employee competencies.